PENGARUH CITRA MEREK, KUALITAS PRODUK DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN DI BURGER KING GRAND WISATA BEKASI - Angelica Oktanami; Verry Cyasmoro (LPPM Universitas Asa Indonesia, 2023)
This stuldy aims to deltelrminel and analyzel thel elffelct of brand imagel, produlct qulality, and pricel pelrcelption on pulrchasing delcisions at Bulrgelr King Grand Wisata Belkasi. Thel data collelction melthod in this stuldy was carrield oult by distribulting qulelstionnairels giveln to 100 relspondelnts with accidelntal sampling telchniqulel. Thel data collelcteld was obtaineld from thel relsullts of qulelstionnairel data collelction which was melasulreld throulgh validity and relliability telsts. Melanwhilel, for thel data analysis melthod, mulltiplel linelar relgrelssion analysis was ulseld with thel hellp of IBM SPSS 25 softwarel, followeld by analysis of deltelrmination coelfficielnts. Thel relsullts of this stuldy indicatel that thel variablels of brand imagel, produlct qulality and pricel pelrcelption simulltaneloulsly influlelncel pulrchasel delcisions at Bulrgelr King Grand Wisata Belkasi. Theln thel relsullts of thel relselarch partially provel that brand imagel, produlct qulality, and pricel pelrcelption havel a significant elffelct on pulrchasel delcisions.